URBAN GROWTH ANALYSIS USING REMOTE SENSING AND GIS TECHNIQUES TO SUPPORT DECISION-MAKING IN ALGERIA—THE CASE OF THE CITY OF SETIF - Slimani, Nabil; Raham, Djamel (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2023)
Rapid urbanization in Algeria is causing significant problems, such as the emergence of unplanned neighborhoods, and local authorities need to apply modern tools like geomatics to monitor and update spatial planning databases to support sustainable development. More to the point, these tools—geographic information systems (GIS) and remote sensing (RS) are of assistance to update the spatial planning and development database so as to support the decision-making. In fact, for understanding the purpose of the process of urban growth in the region of the interior high plateaus, we chose the city of Setif as it represents an urban and economic pole in the region. Besides, economic activities exacerbate the phenomenon of rapid and unplanned urban growth alongside the environmental impact thereof. In the light of the obtained results, there exists a significant increase in urban lands and a significant decline in forests and agricultural lands, as the urban area has tripled from 10.4% in 1985 to 20.3 in 2003 and to 29.7% in 2021. At the same time, the agricultural area has then shrunk from 76.4% in 1985 to 65.8 in 2003 and to 55.5% in 2021, while the forest areas have decreased from 5.04% in 1985 to 4.4 in 2003 and to 2.3% in 2021.